Penerapan Model Teams Games Tournament (TGT) Menggunakan Media Ular Tangga terhadap Hasil Belajar IPS Siswa Kelas V - Handayani, Sekarsuri; Frima, Aren; Andita, Cahyo Dwi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the completeness of the social studies learning outcomes of fifth-grade students at Talang Ubi Elementary School after the Teams Games Tournament learning model using snakes and ladders media was applied. The method used in this study was a quasi-experiment and the research subjects were fifth-grade students of Talang Ubi Elementary School. The instrument used was an essay test question. The results showed that the average Pre-Test score was 35.17. After being treated using the Teams Games Tournament learning model using snakes and ladders media, the Post-Test result was 75.4. If the hypothesis Zcount ≥ Ztable (5.97 ≥ 1.64) then Hα is accepted and Ho is rejected after the Teams Games Tournament model using snakes and ladders media was applied to the social studies learning outcomes of fifth-grade students of Talang Ubi Elementary School, it was stated that it was significantly complete. Keywords: Learning outcomes, Snakes and Ladders Media, Teams Games Tournament